2016
DOI: 10.1002/ardp.201600063
|View full text |Cite
|
Sign up to set email alerts
|

Covalent EGFR Inhibitors: Binding Mechanisms, Synthetic Approaches, and Clinical Profiles

Abstract: Being overexpressed in several types of cancer, the epidermal growth factor receptor (EGFR) is considered one of the key therapeutic targets in oncology. Although many first-generation EGFR inhibitors had been FDA approved for the treatment of certain types of cancer, patients soon developed resistance to these reversible ATP competitive inhibitors via mutations in the kinase domain of EGFR. A new trend was adopted to design covalent irreversible inhibitors, that is, second- and third-generation inhibitors. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 88 publications
0
24
0
Order By: Relevance
“…The action mode of targeted agents is generally predicted through complex computer assisted modeling, followed by biological validation and molecular imaging [24][25][26] . However, intracellular drug interaction may also affect drug efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…The action mode of targeted agents is generally predicted through complex computer assisted modeling, followed by biological validation and molecular imaging [24][25][26] . However, intracellular drug interaction may also affect drug efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Although we could not calculate the accurate incidence of vortex keratopathy following the use of EGFR inhibitors as chemotherapy due to the nature of this study, the condition does not seem uncommon when dealing with recently developed agents. Vandetanib is a second-generation EGFR inhibitor and osimertinib is a third-generation EGFR inhibitor that can target T790 M and EGFR TKI-sensitizing mutations while sparing wildtype EGFR [18]. ABT-414 is an investigational compound.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome acquired resistance caused by T790M, second-generation EGFR-TKIs such as afatinib and dacomitinib have been developed (Table 1) [9,26]. These agents have shown more potent inhibition of TK activity through covalent and irreversible binding to the cysteine at codon 797 (C797) in the TK domain (Fig.…”
Section: Development Of Egfr-tkismentioning
confidence: 99%
“…Osimertinib is a third-generation EGFR-TKI that selectively inhibits mutated-EGFR through irreversible and covalent binding to C797 in the TK domain ( Fig. 4 and Table 1) [9, 26,32,33]. In a phase 3 trial comparing osimertinib with chemotherapy for patients who developed acquired resistance caused by T790M after first-line EGFR-TKI treatment (AURA3 trial), osimertinib showed a superior PFS over chemotherapy (10.1 months versus 4.4 months; hazard ratio [HR], 0.30; P < 0.001) [34].…”
mentioning
confidence: 99%